2013
DOI: 10.1111/jop.12095
|View full text |Cite
|
Sign up to set email alerts
|

IL‐17C and its receptor IL‐17RA/IL‐17RE identify human oral epithelial cell as an inflammatory cell in recurrent aphthous ulcer

Abstract: IL-17C is highly expressed in epithelial cells in RAU lesions, where it seems to stimulate oral keratinocytes via IL-17RA/IL-17RE to produce pro-inflammatory cytokines. Human oral epithelial cells are probably important inflammatory cells in RAU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 24 publications
2
26
0
Order By: Relevance
“…However, Al‐Samadi et al. . reported highly expression of IL‐17C in epithelial cells in RAS lesions.…”
Section: Discussionmentioning
confidence: 97%
“…However, Al‐Samadi et al. . reported highly expression of IL‐17C in epithelial cells in RAS lesions.…”
Section: Discussionmentioning
confidence: 97%
“…Serum levels of IFN-g and IL-17 were significantly increased in RAS patients [48]. Human oral keratinocytes can produce IL-17 and stimulate the production of IL-8 and TNF-a in RAS patients compared with healthy controls [49].…”
Section: Role Of Cytokines In Rasmentioning
confidence: 98%
“…Several immunohistochemical studies using clinical samples have indicated that IL-17C is expressed mainly in the epithelial cells, including for inflammatory bowel disease (IBD) (33,34), chronic obstructive pulmonary disease (20), chronic rhinosinusitis with nasal polyposis (35), and recurrent aphthous ulcer (36). Similar to other tissues, our results revealed that IL-17C was present predominantly in the epithelial cells of H. pylori-infected gastric biopsy specimens as well as in chromogranin A-positive endocrine cells (mainly G cells).…”
Section: Discussionmentioning
confidence: 99%